2022
DOI: 10.1101/2022.03.10.483864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robustness of field studies evaluating biodiversity responses to invasive species management in New Zealand

Abstract: Benefits of invasive species management for terrestrial biodiversity are widely expected and promoted in New Zealand. Evidence for this is presented in policy and scientific reviews of the literature, but the robustness and repeatability of the underpinning evidence-base remains poorly understood. We evaluated the design of field-based studies assessing biodiversity responses to invasive species management in 155 peer-reviewed articles published across 46 journals from 2010 - 2019. Each study was assessed agai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…That is, current predation management frequently assumes positive biodiversity outcomes, yet fails to test hypotheses (Betts et al 2021) that would determine the mechanisms behind observed biodiversity responses. Further, experimentally robust assessments of actual outcomes are rare (Allen et al 2023). For example, we found just one published account of long-term monitoring (defined as > 10 years or three or more 1080 cycles) of a rat-vulnerable bird species following repeated aerial 1080 applications (Robertson et al 2019); current landscape-scale projects conducted under the umbrella of PF2050 are yet to publish any quantitative assessments of native biodiversity responses to predator eradication.…”
Section: Socio-political Influences Shape Conservation In Aotearoamentioning
confidence: 99%
See 4 more Smart Citations
“…That is, current predation management frequently assumes positive biodiversity outcomes, yet fails to test hypotheses (Betts et al 2021) that would determine the mechanisms behind observed biodiversity responses. Further, experimentally robust assessments of actual outcomes are rare (Allen et al 2023). For example, we found just one published account of long-term monitoring (defined as > 10 years or three or more 1080 cycles) of a rat-vulnerable bird species following repeated aerial 1080 applications (Robertson et al 2019); current landscape-scale projects conducted under the umbrella of PF2050 are yet to publish any quantitative assessments of native biodiversity responses to predator eradication.…”
Section: Socio-political Influences Shape Conservation In Aotearoamentioning
confidence: 99%
“…For example, we found just one published account of long-term monitoring (defined as > 10 years or three or more 1080 cycles) of a rat-vulnerable bird species following repeated aerial 1080 applications (Robertson et al 2019); current landscape-scale projects conducted under the umbrella of PF2050 are yet to publish any quantitative assessments of native biodiversity responses to predator eradication. This lack of robust, hypothesis-driven assessment of native species' responses (Betts et al 2021), or adherence to basic principles of good experimental design (Allen et al 2023) makes it difficult to critically test assumptions behind predation-focused management, or to quantify the biodiversity gains it delivers relative to cost.…”
Section: Socio-political Influences Shape Conservation In Aotearoamentioning
confidence: 99%
See 3 more Smart Citations